2018
DOI: 10.1002/ente.201700883
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of a Copper‐Based Methanol Reformer for Fuel Cell Applications

Abstract: Remarkable cycling performance and operation during steam reforming of methanol at 210 °C can be obtained with a CuZnAlOx catalyst supported on the gas diffusion layer of a carbon paper incorporated into the fuel cell anode compartment. Exceptional stability is obtained for at least 100 h under reaction conditions, whereas 10–15 % deactivation is obtained afterwards, in accordance with typical behavior for copper‐based catalysts. Despite that most catalysts of this type suffer from pyrophoricity and sintering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
(135 reference statements)
1
12
0
Order By: Relevance
“…The used catalyst is commercial CuZnAlOx catalyst (HiFuel R120). For practical applications, long‐term stability test of the optimal reformer was carried out under continuous methanol feed at 473 K. It can be seen from Figure that the reformer was quite stable and less than 10% decline in methanol conversion was observed during the 100 hours period, which is similar to the results reported by Joan Papavasiliou et al According to their research, the highly active CuZnAlOx catalyst (HiFuel R120) shows high tolerance under repeated on/off cycles. So the optimized reformer is promising to be integrated into an IRMFC single cell for portable, mobile, and off‐grid applications.…”
Section: Resultssupporting
confidence: 81%
“…The used catalyst is commercial CuZnAlOx catalyst (HiFuel R120). For practical applications, long‐term stability test of the optimal reformer was carried out under continuous methanol feed at 473 K. It can be seen from Figure that the reformer was quite stable and less than 10% decline in methanol conversion was observed during the 100 hours period, which is similar to the results reported by Joan Papavasiliou et al According to their research, the highly active CuZnAlOx catalyst (HiFuel R120) shows high tolerance under repeated on/off cycles. So the optimized reformer is promising to be integrated into an IRMFC single cell for portable, mobile, and off‐grid applications.…”
Section: Resultssupporting
confidence: 81%
“…[47][48][49][50][51] Recently, we have demonstrated that this objective can be also achieved via in-situ electrochemical pumping of H 2 in an internal reforming methanol fuel cell, where at atmospheric pressure and low temperatures in the range of 200-210°C, the equilibrium methanol conversion is close to 100 %. [22,27,31,[52][53][54] In addition to that, inhibition of the reaction rate by the produced carbon monoxide is minimized since its concentration is well below the WGS equilibrium and follows secondary pathways, however all the kinetic reports on SRM process do not contain a relative parameter in the proposed equations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this type of fuel cell can also tolerate high concentrations of CO, as high as 2 vol.%, in the reformed hydrogen-rich gas stream, thus making the methanol fuel processor more simple and lighter in weight and volume, since both WGS and PROX catalytic reactors and the accompanied heat exchangers and other peripherals will not be necessary [1,2]. Recently, Avgouropoulos et al [1][2][3][4][5] demonstrated the functionality of an Internal Reforming Methanol Fuel Cell (IRMFC), where the methanol gets reformed by a Cu-based catalyst incorporated into the anode compartment of HT-PEMFC. This option offers more room for simplification of the design and control of a compact power unit, which will be very attractive for portable and off-grid applications.…”
Section: Introductionmentioning
confidence: 99%
“…Steam Reforming of Methanol (SRM) is an endothermic catalytic process that provides at relatively low temperatures (<250 • C) and ambient pressure, a hydrogen-rich gas stream (hydrogen up 75%) with low CO concentration (usually around 1-2%; mainly produced via methanol decomposition or/and reverse-WGS, thus diminishing hydrogen selectivity of SRM process) [6][7][8][9] exchangers and other peripherals will not be necessary [1,2]. Recently, Avgouropoulos et al [1][2][3][4][5] demonstrated the functionality of an Internal Reforming Methanol Fuel Cell (IRMFC), where the methanol gets reformed by a Cu-based catalyst incorporated into the anode compartment of HT-PEMFC. This option offers more room for simplification of the design and control of a compact power unit, which will be very attractive for portable and off-grid applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation